Thermal, mechanical and degration behaviours of plasticized polylactic acid/starch blends - Awale, Raina Jama (Kulliyyah of Engineering, Internatinonal Islamic University Malaysia, 2016)
Petroleum based plastics have raised environmental concerns due to their non-degradable behaviour. To overcome this problem, biodegradable based materials have been researched extensively to be used as alternative materials. Polylactic acid (PLA) is a thermoplastic polymer produced from renewable resources. However, PLA's brittleness and slow degradation rate restricted its applications. The aim of this research is to improve the flexibility of PLA by using environmentally friendly plasticizer and filler. In this research, plasticized PLA/starch composites were developed using 5, 10, 15 and 20 wt% of epoxidized palm oil (EPO) contents. The blend was prepared using two methods ;(1) solution casting methods, where the blends were dissolved in chloroform and casted to evaporate the solvent and (2) melt blending method, where the blends were melt blended using internal mixer. Samples prepared in both methods were hot pressed for characterization purposes. The effects of the processing methods on the thermal behaviours of PLA/starch/EPO (PSE) prepared were evaluated using Differential Scanning Calorimetry (DSC). From DSC thermogram, the addition of 10wt% of EPO to PLA/starch (PSt) decreased the glass transition (Tg) from 58.5 ˚C to 52.5 ˚C and 54 ˚C for casted ad melt blended PSE respectively due to plasticizing effect of EPO. The crystallization temperature (Tcc) and melting temperature (Tm) of PSt decreased from 118.3˚C and 151.5˚C to 109˚C and 147.1˚C for casted PSE and 105˚C and 145.5˚C for melt blended PSE respectively, suggesting EPO facilitated easier crystallization for PSE. Based on the DSC result and processing condition, melt blending process was selected to further characterize PSE blends. From Thermogravimetric Analysis, the maximum degradation temperature of PSt from 346˚C to 384˚C was attributed to EPO acting as heat resistance. The mechanical testing revealed EPO at 5, 10 15 and 20 wt% decreased Young's Modulus from 2776 MPa for PSt to 797, 2496, 727 and 267 MPa, respectively. The elongation-at-break increased at all EPO content. This result indicated that EPO increased the ductility of PSE blends. The impact strength of PSt increased from 28 kJ/m2 to 30, 51, 37, 38 kJ/m2 at 5, 10, 15 and 20 wt% EPO which could be due EPO acting as energy distributer allowing more energy to be absorbed during sudden shock. The storage modulus decreased as the damping factor increased by the addition of EPO to PSt attributed to the increase in the elastic response of PSE blends. The shift of absorption band of PSt at 1748, and 1182 cm-1 to Fourier Transform Infrared Spectroscopy (FT-IR) to lower wavenumber in the presence of EPO could indicate the PSE blends were physically blended. The morphological study evidenced ductile fracture of PSE with 10 wt% EPO compared brittle morphology of PSt. As for the biodegradability study, the weight loss of PSt increased with the increases of EPO content which could be attributed to moisture penetration into PLA matrix and triggering hydrolysis in PLA chains. From these results it can be concluded that EPO enhanced the mechanical, thermal properties and increased the biodegradability of PLA.